Optimization of Palm Oil Fuel Ash (POFA) Content as Cement Replacement Based on Strength and Porosity - Abdul Wafi, Razali; Afzan, Ahmad Zaini; Nur Fadilah, Darmansah; Siti Halipah, Ibrahim; Nadia, Zaini; Sitti Diana, Tamjehi; Gui, Hun Chuen (Trans Tech Publications Ltd., 2020)
The usage of agricultural waste in form of ashes as one of the constituent materials in concrete has been studied in recent years. Palm Oil Fuel Ash (POFA) is one of the largest agricultural wastes produced in Malaysia that contain high amount of silica with pozzolanic properties. The mass production of POFA are typically disposed to open area and in turn can generate environmental issues and health hazards. Due to the waste disposal problem, a number of initiatives have been done by utilizing POFA into various construction materials including as substitute to Ordinary Portland Cement (OPC) in concrete production. This paper discusses on the water absorption properties and compressive strength of concrete by utilizing POFA in several series of cement replacement. OPC was replaced by POFA at 2.5%, 5%,7.5% and 10% in these series of mix design. Control OPC concrete sample was also prepared for comparison. The samples were prepared in 100 mm cubic moulds and tested for compressive strength and water absorption for 7, 14 and 28-day curing ages. Three replicates were prepared for each concrete mix and for each test conducted. The results stipulated that the higher percentage of POFA replacement decreased the compressive strength and increased the water absorption amount of concrete mixture over different concrete ages.